A nutritional analysis of elite pre-adolescent swimmers - MacLaren, D. P.; Harte, J. E.; Hackett, A. F. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Information about habitual food intake of pre-adolescent children of an elite swimming group and a non-active control group was systematically obtained. Thirty swimmers (15 male and 15 female, mean age 12.2 ± 0.9 years) trained an average of five times a week (approximately 9 h) and were competing at National level. The control group (15 male and 15 female, mean age 11.9 ± 0.7 years) consisted of normally active children. Measurement of weighed food intake was conducted over three days. The total energy intake and the protein intake for swimmers were significantly higher (P < 0.05 and P < 0.001 respectively), than those of the control group. No significant differences were apparent between the groups for fat and simple and complex carbohydrate intakes. When compared to recommended daily allowances (RDAs), both groups were found to have significantly lower fat intakes and significantly higher protein and total carbohydrate intakes than normal (P < 0.01). Recommendations to the swimmers were to increase carbohydrate intake and further reduce fat consumption so that the possibility of lowered glycogen stores would be minimised.